Critical Challenges in Rechargeable Aprotic Li–O2 Batteries. Issue 9 (24th February 2016) - Feng, Ningning; He, Ping; Zhou, Haoshen
Abstract : Rechargeable aprotic Li–O2 batteries are one of the most promising next‐generation battery technologies that can deliver extremely high energy density. In the past decades, this technology has attracted worldwide attention, and considerable progress has been achieved. However, numerous critical scientific challenges remain to be solved for practical applications. A specific discussion of recent progress from the perspective of the stable aprotic Li–O2 system with high energy efficiency is presented. The discussion is highlighted on the reaction mechanisms on air cathode, stability of cell components in semi‐open surroundings, and improvement of battery performance by catalyst design. Challenges and perspectives are also presented. This study provides an intensive understanding of aprotic Li–O2 batteries and offers an important guideline for developing reversible and high‐efficiency Li–O2 batteries. Abstract : Aprotic Li–O2 batteries have attracted worldwide interest due to their extremely high energy density. The development and critical challenges of Li–O2 batteries are summarized from the perspective of the unique electrochemistry involving the stability of aprotic electrolytes, the three‐phase reactions on the cathodes, and the dissolution/deposition reactions on the anodes.